Effectiveness and treatment moderators of parenting interventions in Finnish perinatal primary care - Flykt, Marjo; Kilpeläinen, Markku; Kinnunen, Susanne; Salonen, Markus; Peltonen, Kirsi; Isosävi, Sanna; Lindblom, Jallu (WILEY, 2026)
Perinatal parenting interventions may be important for enhancing parenting quality, but previous research has mostly focused on parental sensitivity. Other important outcomes, such as parental self-efficacy (PSE), have rarely been studied. Research is also contradictory on whether parenting interventions can also enhance maternal mental health and how treatment-related moderators affect treatment outcome. In this study, we examined the effectiveness of three individually tailored perinatal parenting interventions (therapeutic parent-infant work, maternity and child health clinic psychologists, and practical help) for parenting and mental health in naturalistic community settings in Finnish primary care. We further examined whether mental health symptoms moderated parenting efficacy and how treatment-related factors moderated parenting and mental health outcomes. The sample comprised 263 Finnish-speaking mothers: 177 in different interventions and 86 non-clinical controls from the same area. Parenting was examined with Maternal Self-Efficacy Scale and Emotional Availability (EA) self-report, depression with Edinburgh Postnatal Depression Scale and anxiety with Overall Anxiety Severity and Impairment Scale at the beginning of treatment, post-treatment, and at the six-month follow-up. Therapeutic work was the most broadly effective, with long-term effects on both parenting and mental health outcomes, regardless of maternal symptom level. Spouse participation, postnatal onset, and higher treatment dosage increased intervention effectiveness.